Preparation and characterization of immobilized mannanase on polyhydroxyalkanoate (PHA) - Zhiyue Men; Yafei Zhang; Zhao Pang; Tao Li; Hening Zhang; Yue Zhou; Ning Hao; Yajian Song; Yu Bai (Bioresources and Bioprocessing)
Abstract Galactomannan oligosaccharides (GMOS), composed of 2–10 mannose units linked with β-1, 4 glycosidic bond as the main chain and galactose linked with α-1, 6 glycosidic bond as the side chain, are crucial for probiotic food synthesis due to their ability to promote the growth and activity of beneficial intestinal microbiota, enhance the host immune system, and improve nutrient digestion. GMOS is usually obtained by hydrolyzing plants such as locust bean gum and guar gum with mannanase. β-mannanase ManA from Alkaliphilic Bacillus sp. N16-5 can hydrolyze β-1, 4 glycosidic bond of galactomannan. In this study, an immobilization system was employed utilizing polyhydroxyalkanoate (PHA) biopolymers, which naturally have an affinity mainly mediated by hydrophobic interaction for PhaP protein. Fusion protein combining ManA with PhaP from Aeromonas hydrophila, was subsequently immobilized on PHA support to form a multi-enzyme complex, facilitating the hydrolysis of locust bean gum to generate GMOS. This immobilized enzyme enhances enzyme stability and reusability, can be reused up to 32 times while maintaining ~ 80% of its activity, offering substantial cost savings through in-situ enzyme and product separation. Additionally, the different PHA forms were developed to hydrolyze locust bean gum to produce GMOS, such as nano PHA particles, PHA electrospun materials, while these preliminary investigations show promise, further research is needed to optimize their performance and practical application. Graphical Abstract